Investigating d-lysine stereochemistry for epigenetic methylation, demethylation and recognition. Issue 99 (29th November 2017) - Belle, Roman; Al Temimi, Abbas H. K.; Kumar, Kiran; Pieters, Bas J. G. E.; Tumber, Anthony; Dunford, James E.; Johansson, Catrine; Oppermann, Udo; Brown, Tom; Schofield, Christopher J.; Hopkinson, Richard J.; Paton, Robert S.; et al.
Abstract : Writers, erasers and readers show the selectivity for the acceptance of (methyl)d -lysine. Abstract : Histone lysine methylation is regulated by N ε -methyltransferases, demethylases, and N ε -methyl lysine binding proteins. Thermodynamic, catalytic and computational studies were carried out to investigate the interaction of three epigenetic protein classes with synthetic histone substrates containingl - andd -lysine residues. The results reveal that out of the three classes, N ε -methyl lysine binding proteins are superior in accepting lysines with thed -configuration.